2016
DOI: 10.24189/ncr.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

Camera-trap monitoring of Amur Tiger (Panthera tigris altaica) in southwest Primorsky Krai, 2013–2016: preliminary results

Abstract: Southwest Primorsky Krai retains the sole remaining population of critically endangered Amur leopards, but and also holds an isolated population of Amur tigers. This small group of tigers plays a key role as a core breeding population for potential Amur tiger recovery in neighboring Jilin and Heilongjiang Provinces of Northeast China. A large scale camera-trap monitoring program initiated by the United Administration of the State Nature Biosphere Reserve Kedrovaya Pad and Land of the Leopard National Park in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…In 2007, only 11-13 individuals (four males, four females, and 3-5 individuals of unknown sex and age) were identified by the traditional winter tracking method in the same area (Pikunov et al, 2009). Later estimation of tiger numbers in this region, which was based on monitoring with camera traps, showed results that were similar to our data (Matiukhina et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In 2007, only 11-13 individuals (four males, four females, and 3-5 individuals of unknown sex and age) were identified by the traditional winter tracking method in the same area (Pikunov et al, 2009). Later estimation of tiger numbers in this region, which was based on monitoring with camera traps, showed results that were similar to our data (Matiukhina et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The camera trap method, due to high labor and material costs (Riley et al, 2017), is more suitable for use in small study areas, limited in size by protected areas and hunting tenures. A significant downfall of this method is the extremely rare dedection of tiger cubs by camera traps, noted in the previous surveys (Soutyrina et al, 2013;Matiukhina et al, 2016) and associated with the rather secretive lifestyle of family groups. Females with cubs, for example, rarely visit objects of intra-and interspecific indirect communication such as mark trees (Kolchin & Soutyrina, 2012) that are traditionally prime locations for setting up camera traps.…”
Section: Discussionmentioning
confidence: 98%
“…Using the fecal DNA and a panel of 12 microsatellites amplified in three multiplex PCR reactions, we successfully identified 24 unique Amur leopard individuals, which include 18 males and 6 females. These represent approximately a quarter of the Amur leopard population of the Land of the Leopard [ 21 , 45 ]. The greater number of males was in contrast to the findings of a camera trap study conducted in the Southwest of Primorsky Krai, which reported a male to female ratio of 1:1.2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Habitat loss, landscape fragmentation, prey depletion and poaching have contributed to the decline of the Amur tiger from more than 3,000 to about 500 during the past century 1 – 3 , while the Amur leopard, to less than 100 individuals 4 . The Amur tigers are currently existing in two separate populations: a larger one in the Sikhote-Alin Mountains of Russia (415–490 individuals) 5 , 6 , and a much smaller one, almost isolated from the larger one, in southwestern Primorsky Krai, Russia, and the nearby Hunchun region in China 4 , 7 , 8 . The Amur leopards occur as a small single population co-existing with the smaller tiger population 6 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%